SDGs Social Disclosure: Symbolic and Substantive Analysis of Islamic Banks 2021–2023 - Muhammad Yusuf Fadhillah; Elvia R. Shauki (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates how five Indonesian Islamic banks (BSI, BMI, BTPS, BAS, and PDSB) disclose social aspects in their sustainability reports from 2021 to 2023. The analysis focuses on GRI indicators 401–419 that are aligned with the social pillar of the Sustainable Development Goals (SDGs), specifically SDG 4, 5, 10, 11, 16, and 17. Employing qualitative content, thematic, and constant comparative analysis, the study utilizes indexing based on five criteria: quantitative disclosure, concrete actions, specificity and relevance, consistency, and transparency. The findings reveal that BMI, BSI, and BTPS demonstrate high levels of commitment, as indicated by indexing results of 60–80%, 52–57%, and 45–50%, respectively. These disclosures are supported by valid and strong evidence, indicating substantive reporting. In contrast, BAS and PDSB show lower levels of commitment, with indexing scores of 0–54% and 0%, respectively. The narrative content in their disclosures lacks solid supporting evidence, suggesting a symbolic rather than substantive reporting. From the perspective of institutional theory, BSI, BMI, and BTPS reflect the influence of coercive and normative pressures, as shown by compliance with regulations such as POJK 51/2017 and the consistent adoption of the GRI-based reporting structure. Conversely, BAS and PDSB are more influenced by coercive and mimetic pressures, demonstrated by minimal disclosures that tend to imitate other reports without internalizing sustainability principles.